Too much free speech? - Bezanson, Randall P. (University of Illinois Press, 2012)
The author takes up an essential and timely inquiry into the Constitutional limits of the Supreme Court's power to create, interpret, and enforce one of the essential rights of American citizens. Analyzing contemporary Supreme Court decisions from the turn of the twenty-first century, the author argues that judicial interpretations have fundamentally and drastically expanded the meaning and understanding of "speech." The author focuses on judgments such as the much-discussed Citizens United case, which granted the full measure of constitutional protection to speech by corporations, and the Doe vs. Reed case in Washington state, which recognized the signing of petitions and voting in elections as acts of free speech. In each case study, he questions whether the meaning of speech has been expanded too far and critically assesses the Supreme Court's methodology in reaching and explaining its expansive conclusions. --